2020
DOI: 10.26803/ijlter.19.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Covid-19 Awareness, Distance Learning Education Experiences and Perceptions towards Institutional Readiness and Challenges

Abstract: Amidst the threat of COVID-19 pandemic in the Philippines, the educators, students, and the school are still coping and adjusting to the distance learning education. This study explored teachers' awareness about the COVID-19 pandemic and their opinion on their respective schools' readiness, as well as their response to the challenges of conducting distance learning education in the Philippines. A validated questionnaire was developed to collect the relevant data for this study. The initial reliability test obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
1
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(198 citation statements)
references
References 19 publications
7
120
1
16
Order By: Relevance
“…For instance, where their home situation does not provide the optimal environment for online instruction, academics in most scenarios can use their offices and/or classrooms. In contrast, depending on the location, some basic education schools may lack the facilities and training even if they are located in urban areas (Lapada et al, 2020). Institutional training and backing as well as social support had been found to determine the successful adoption of e-learning in the past (Singh, Naz, & Narayan, 2017).…”
Section: Level or Type Of School At Which The Instructors Taughtmentioning
confidence: 99%
“…For instance, where their home situation does not provide the optimal environment for online instruction, academics in most scenarios can use their offices and/or classrooms. In contrast, depending on the location, some basic education schools may lack the facilities and training even if they are located in urban areas (Lapada et al, 2020). Institutional training and backing as well as social support had been found to determine the successful adoption of e-learning in the past (Singh, Naz, & Narayan, 2017).…”
Section: Level or Type Of School At Which The Instructors Taughtmentioning
confidence: 99%
“…The research of Purwanto et al [1] stated that not all teachers were proficient in using internet technology in some locations. Other problems include: 1) teachers that only focus on giving assignments without explaining the subject first [2]; 2) students starting to experience online learning boredom [3]; 3) online learning requiring a lot of money [4]; and 4) different regional conditions [5]. This could become a hindrance during online learning process.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Fedina et al, (2017) concluded in their study that preschool educational institution (PEI) administration considers their educational institution ready for distance learning technology (DET). However, from the paper of Alea et al, (2020), they explained that the teachers' geographical location correlates to the readiness to adapt to distance learning education. Table 3 Perceived Challenges on the Delivery of Distance Learning Perceived Challenges Frequency Rank Internet connection/ connectivity 18 1 Teachers' competence and skills for online learning delivery 11 2 Availability of funds and/ or budget for online/ distance learning 10 3 Availability of gadgets and/ or devices like cellular phones and/ laptop for learning and teaching 9 4…”
Section: Resultsmentioning
confidence: 99%